What's in a name? An experimental examination of investment behavior - Lucy F. Ackert; Bryan K. Church; James Tompkins; Ping Zhang (Federal Reserve Bank of Atlanta, 2003)
A fundamental unresolved issue is whether information asymmetries underlie investors' predisposition to invest close to home (i.e., domestically or locally). The authors conduct experiments in the United States and Canada to investigate agents' portfolio allocation decisions, controlling for the availability of information. Providing participants with information about a firm's home base, without disclosing its specific identity, is not sufficient to change investment behavior. Rather, participants need to know a firm's name and home base. Additional evidence indicates that participants are more familiar with securities in which they chose to invest than other securities. Familiarity is a key determinant of investment behavior.
Keywords: 330; Financial markets; Investments; Investments; Foreign